(untitled) (PerCursos, 2021)
This article exposes the trajectory of a Portuguese musician - Tó Trips - and his last band - Dead Combo - in order to merge a musical path with a sound landscape in the line of Schafer’s concetualization (2012). By helping us, in methodological terms, with a life history and documentary materials, we will establish a synchrony between city, sounds and social actors. Dead Combo and Tó Trips are, in the framework of this article, the (re)creators of a sound landscape of Lisbon, allowing, simultaneously, to establish some assertions about the value of sound and music as fuels of collective and individual identities; and the potentiation of the construction of symbolic and affective imaginaries in the face of a certain urban space in Frith’s path (1996). In a process that some call spatial turn (STAHL, 2004) in the last decades, we will show that globalization seems to have renewed the emphasis on the local, encouraging reconstructions of identities through the emergence of new expressions of attachment to the city and, therefore, a re-imagination of the city, starting from an artistic production territorially anchored, lived and felt. And such an emphasis seems to be assuming a critical urgency in these pandemic times.